Entrepreneurship and management in an Islamic context - Ramadani, Veland (Springer, 2017)
Annotation The aim of this volume is to explore entrepreneurship and business from the perspective of Islamic principles, which are usually based on collaboration, teamwork, generosity and altruism. The contributions deal with the confluence of Islamic principles with entrepreneurial and business ownership characteristics; resource use by entrepreneurs; means of entrepreneurial success, and ethics and social responsibility.
Keywords: Entrepreneurship -- Religious aspects -- Islam.; Management -- Religious aspects -- Islam.; elektronické knihy; electronic books